Person-Centered, Skilled Services Using a Montessori Approach for Persons with Dementia - Douglas, Natalie; Brush, Jennifer; Bourgeois, Michelle (Seminars in Speech and Language, 2018)
The current mandate for person-centered care throughout the health care system, and especially in the nursing home industry, requires that speech–language pathologists ensure that the services they provide to elders with dementia are skilled, person centered, and relevant to positive overall health outcomes. Guidelines developed by the Association Montessori International Advisory Board for Montessori for Aging and Dementia are one avenue toward such skilled and person-centered services. The purpose of this article is to provide clinicians with practical strategies for guiding their assessment, goal writing, and intervention plans to meet the expectations of a person-centered approach to services for elders with dementia, using the Montessori approach as a philosophical guide.
Keywords: person-centered care; dementia; Montessori approach; elders